New gas processing technologies for nitrogen rejection and helium capture - May, E.F.; Xiao, G.; Weh, R.; Arami-Niya, Arash; Wang, Y.; Manning, D.; Li, G. (2019)
Nitrogen is a common impurity in natural gas that seems benign, at first, but is in fact quite pernicious for LNG producers. If the feed to an LNG plant contains several percent N2 then a dedicated separation process is required to meet product specifications. However, because N2 and CH4 are so similar, the conventional method of separation is cryogenic distillation at the very end of the LNG train. This leads to higher capital and operating costs than if N2 could be separated earlier in the process due to increased vessel sizing and parasitic refrigeration load. The only practical source of helium is natural gas, where it exists as a difficult-to-recover trace impurity. Helium’s price is increasing rapidly because of its importance in industrial, medical and scientific applications and its limited availability. It can represent a significant source of revenue to an LNG plant despite the costly extra cryogenic processes required to capture it. Three new adsorption-based technologies are described which enable ambient nitrogen rejection from natural gas, dilute methane enrichment to drive gas-engines, and helium capture from end-flash gas. These technologies are founded on two novel adsorbents with record selectivities for methane or helium. The separation power of these materials is greatly amplified using Dual-Reflux Pressure Swing Adsorption cycles beyond that achievable with conventional adsorption processes. Results from field trials underway in China as well as laboratory data measured over a wide range of conditions will be presented for these new gas processing technologies.